2011
DOI: 10.1080/02681102.2010.537252
|View full text |Cite
|
Sign up to set email alerts
|

Developing women: why technology can help

Abstract: The paper introduces a concept of household production technology that shows why Internet and communication technology (ICT) have the potential to increase the equity and efficiency of female participation in the labor force. Since inputs of female labor are required at short intervals in the production of the household good, female labor supply and earnings in the production of external goods fall below those of males. Household consumption at a point in time is maximized, but loss of potential learning-by-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
1
13
0
2
Order By: Relevance
“…Brady, 2005) wherein women feel supported and can increase the size and diversity of their information networks. For example, Goyal (2011) suggested that creating women-only Internet cafes can help women find information through online support groups and message boards. However, absent sufficient access to the Internet, radio remains the only feasible technology through which women in developing nations, who are more likely to be impoverished and illiterate, can be targeted following disasters.…”
Section: Demographics and Information Repertoires In Haitimentioning
confidence: 98%
“…Brady, 2005) wherein women feel supported and can increase the size and diversity of their information networks. For example, Goyal (2011) suggested that creating women-only Internet cafes can help women find information through online support groups and message boards. However, absent sufficient access to the Internet, radio remains the only feasible technology through which women in developing nations, who are more likely to be impoverished and illiterate, can be targeted following disasters.…”
Section: Demographics and Information Repertoires In Haitimentioning
confidence: 98%
“…A growing body of studies shows that the impact of ICTs is increasingly related to women's empowerment, both in economic and social and cultural respects. It is argued that ICTs allow women to transform knowledge and information into innovative products and services (Ambujam & Venkatalakshmi, 2009;Beyond Access, 2012;Levis, 2011), and increase the flexibility of their participation in the labor supply, e.g., through facilitating distance work and flexi-time (Goyal, 2011). Moreover, ICTs help in creating women's leadership, and participation in community and economic development (Anitha & Sundharavadivel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ICT also has the potential to increase the equity and efficiency of female participation in the labour force (Goyal 2011). It helps restore flexibility in female external labour supply, which could be constrained by household responsibilities, since it facilitates distance work, flexi-time and location activity, making it easier to match skills to jobs, and to maintain and upgrade skills.…”
Section: An Analytical Frameworkmentioning
confidence: 99%